An Italian Explorative Study of Willingness to Pay for a New Functional Pasta Featuring Opuntia ficus indica - Nadia Palmieri; Walter Stefanoni; Francesco Latterini; Luigi Pari (Agriculture, 2021)
Opuntia ficus indica is a source of vitamins and minerals, and recently, it has been used as ingredient to make a new functional pasta. Italy produces the highest amount of pasta in the world and it is also the second-highest producer of opuntia globally. This study sought to identify the consumer willingness to pay for pasta featuring Opuntia ficus indica and to understand what factors influence their choice. This study is the first in food research to analyze consumers’ willingness to pay for a new functional pasta featuring Opuntia ficus indica. Data were collected by using a web-based survey; the sample was composed of 342 consumers and an ordered logistic regression model was applied. The findings showed that the educational and higher income levels of respondents play important roles in the willingness to pay for functional pasta. Moreover, the healthy and nutritional features of functional pasta together with the respondents’ willingness to eat it, their curiosity towards this new food and their need to get more information about functional pasta should improve consumers’ willingness to pay for it. The findings should be useful for firms to draw marketing strategies considering the positive consumers’ attitude toward the use of Opuntia ficus indica in pasta production.